Case report describing late balloon dilatation as a treatment for paravalvular leak with intuity elite rapid deployment valve. Issue 3 (20th December 2019) - Pal, Nikhil; Jones, Dylan; Rice, Gregory; Sinhal, Ajay
Abstract: Use of sutureless bioprostheses for aortic valve replacement has increased in recent years as compared to conventional prostheses, though with the potential issue of paravalvular leak, which requires close follow‐up. We present this case report describing the successful treatment of paravalvular leak in a 65 year old man, who had NYHA class III symptoms post implantation of a 21 mm Intuity Elite rapid deployment bioprosthesis (Edwards Lifesciences, Irvine, CA). Diagnosis was established using TTE, TOE, and Cardiac MRI. Performing balloon dilatation using an Atlas Gold balloon (BARD Peripheral Vascular Inc., Tempe, AZ) treated the likely inadequate expansion of the subvalvular stent, leading to significant reduction in the paravalvular leak. At one month follow‐up patient reported complete resolution of his symptoms. Successful percutaneous treatment of paravalvular leak following implantation of rapid deployment sutureless bioprosthesis provides a new treatment strategy for these patients; this strategy requires further validation.